A Case-Based Critical Care Curriculum for Internal Medicine Residents Addressing Social Determinants of Health - Deepa Ramadurai; Ellen E. Sarcone; Mark T. Kearns; Anna Neumeier (Association of American Medical Colleges, 2021)
Introduction Graduate medical education on social determinants of health (SDOH) is limited. Residents often directly care for vulnerable populations at safety-net hospitals, yet curricula thus far are based in the ambulatory setting. Methods We developed a case-based curriculum integrating SDOH with critical care topics to standardize knowledge and improve skills and attitudes of internal medicine residents working with these patients. We conducted a needs assessment, identified systematic social risk domains, and modified a published curriculum to develop the content. Case-based discussions were conducted weekly in the medical intensive care unit, while knowledge, attitudes, and skills were assessed daily during multidisciplinary rounds. A 360-degree assessment was completed with pre- and postcurriculum surveys and self-reflection. Results Eleven residents completed postcurriculum surveys. Both pre- and postcurriculum, residents reported confidence in identifying and describing how SDOH affect care. After the curriculum, residents could name more resources for patients experiencing health disparities due to substance abuse (pre: 47%, post: 73%) and financial constraints (pre: 50%, post:64%). This curriculum was recognized as the first training many residents received (pre: 31%, post: 91%) with formal feedback (pre: 16%, post: 64%). Discussion Implementing a curriculum of social risk assessment in critically ill patients was difficult due to competition with clinical care. Participating residents said they "loved the open dialogue" to reflect on their experiences; this became an avenue to "debrief on specific patient encounters and [how] SDOH brought [patients] to the ICU." Future directions include qualitative analysis of reflections and assessment of curricular impact on trainee resiliency.